Technology surveillance, transformative thinking, competitiveness and organizational scenery: Reflection on the actors - Monsalve Ospina, Juan David; Castro Álvarez, Jhon Freddy (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This article concentrates preliminary results of the research “Observatory Technological Institute of Administrative and Accounting Sciences for Colombia”, a project that is being fully financed by the Corporación Universitaria U De Colombia, the general objective of the research is “Analyze the viability of the implementation of a Technological Surveillance System -OTeCH CAC- “. One of the main results found so far, is that SMEs must understand that it is not enough to do efforts to organize, order and classify the information obtained from its production processes, but must be given proper management.